OP0141-HPR An innovate measurement instrument to assess activity limitations in hip and knee osteoarthritis: the computerized animated activity questionnaire (AAQ) and its psychometric properties. (15th June 2017) - Peter, W; Vet, R de; Boers, M; Harlaar, J; Roorda, L; Poolman, R; Scholtes, V; Steultjens, M; Roos, E; Guillemin, F; Benedetti, MG; Martinez, A Escobar; et al.
Abstract : Background: The Animated Activity Questionnaire (AAQ) measures activity limitations in hip and knee osteoarthritis (HKOA), and was developed in close collaboration with patients 1 . Previously we showed an adequate construct- and cross-cultural validity of the AAQ 2 Objectives: To determine the reliability, responsiveness and interpretability of the AAQ. Methods: In 6 European countries the AAQ was completed twice on a computer with a 7 days interval by 238 patients (DK (36), FR (37), IT (51), NL (39), SP (36), UK (39)). Reliability was assessed by calculating internal consistency (Cronbach's alpha), the intra-class correlation coefficient (ICC), the Standard Error of Measurement (SEM) and the Smallest Detectable Change (SDC). In the Netherlands, an additional group of 92 patients were followed for 6 months in order to assess responsiveness. Data from the AAQ, a PROM (the Hip disability or Knee injury Osteoarthritis Outcome Score, ADL subscore), and performance-based tests (the Timed Up and Go test, Stair Climbing Test and 30 seconds Chair Stands Test) were collected. To estimate the Minimal Important Change (MIC) of the AAQ an anchor-based MIC distribution method was used with a Global Rating of Change (GRC) as anchor. The Receiver Operating Characteristic (ROC) method was used to find the AAQ change score that best discriminates between patients who improved in activity limitations and who are not. The MIC was compared to the SDC in order to facilitate the interpretation of change scores. Results: Cronbach's alpha was o.94. ICC for test-retest reliability was 0.93 (95% CI: 0.91–0.95). SEM and SDC were 4.9% and 13.5%, respectively. With regard to responsiveness the change scores of the AAQ after 6 months correlated 0.58 with the PROM, 0.42–0.55 with the performance based tests, and 0.46 with GRC. The ROC curve showed an area under the curve of 0.72 with a sensitivity of 63% and a specificity of 81% for the optimal MIC of 9.1 for discrimination. The MIC was smaller than the SDC meaning that the change is important but cannot be distinguished from measurement error in individual patients. Conclusions: The AAQ, measuring a new construct in the domain physical functioning in addition to a PROM and performance-based tests, showed good construct validity, cross-cultural validity, internal consistency and test-retest reliability. A change in AAQ score over 13.5% indicates a real improvement in activity limitations in HKOA patients. The AAQ seems to have great potential for international use in research but the application in clinical practice needs caution. References: Peter WF et al. Arthritis Care Res (Hoboken). 2015 Jan;67(1):32–9. Peter WF et al. Arthritis Care Res (Hoboken). 2016 Oct 16. Disclosure of Interest: None declared